THE TRANSFORMATION OF RESIDENTIAL SPATIAL AND FORM IN KAUMAN VILLAGE YOGYAKARTA - Amos Setiadi; C. Dwi Astuti Depari (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2021)
Kauman village becomes a symbol of the Javanese philosophy and the Islamic ideology on which the local society orient their faith. This research aims to find the residential transformation factors and form in Kauman village in Yogyakarta and the characteristic of each object to conserve Kauman village as a constituent element that defines Yogyakarta City's identity. This research method is qualitative – descriptive research using a synchronic approach to present synthetic results from each object and detailed object characteristics conducted in a certain period. All data are collected by doing observation and interviewing second parties. The discussion led to the residential spatial change as an adaptation form of Batik skipper's and Ketib's residence in Kauman village of Yogyakarta. It can be concluded that the identity of the residents as a part of a modern community is gradually more dominant than the desire to reveal their identity as a part of a traditional Javanese community. Nevertheless, Batik skipper's residences retain Javanese architecture and Indische architecture characteristics as a symbol of the social status of the Batik Skipper and Ketib; The space for religious activities is no longer available in Batik skipper's residence. On the contrary, it is available in Ketib's home, where the residents still retain the function of langgar, which is located in the highest privacy zone.